The Effect of Project-Based Learning Method on Creative Problem-Solving in Students of the Entrepreneurship Study Program, Indonesian University of Education - Sabrina Khaerunnisa; Azizah Fauziyah; Mira Nurfitriya (Jurnal Indonesia Sosial Teknologi, 2024)
The effectiveness of learning is significant in preparing students' skills paradigms. This research aims to instill the influence of the Project Based Learning (PjBL) method on students' Creative problem-solving abilities in the context of entrepreneurship learning. This research focuses on Indonesian Education University Entrepreneurship Study Program students who have taken the Start-up course. Creative problem-solving skills are considered important in preparing students to face the demands of an increasingly complex world of work. The research method used is quantitative with a descriptive verification approach, and data collection is carried out through questionnaires. The results of the research show that project-based Learning (PjBL) has a significant influence on increasing creative problem-solving abilities in students of the Entrepreneurship Study Program at the Indonesian University of Education. This research shows that Project Based Learning significantly improves the quality of Creative Problem Solving for Entrepreneurship Study Program Students at Universitas Pendidikan Indonesia